Establishing a hawkish reputation: Interest rate setting by newly appointed central bank governors - Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
In this paper, we explore the interest rate setting behavior of newly appointed central bank governors. We use the Kuttner and Posen (2010) sample, which covers 15 OECD countries, and estimate an augmented Taylor (1993) rule for the period 1974-2008. We find, first, that newly appointed governors fight inflation more aggressively during the first four to eight quarters of their tenure in an effort to establish a reputation for being inflation averse. Second, we find a significantly stronger reaction to inflation by newly appointed governors working within monetary policy frameworks comprised of an at least partly independent central bank and an explicit nominal anchor.
Keywords: E31; E43; E52; E58; 330; Central bank governors; credibility; inflation; monetary policy; reputation; Taylor rules